1996
DOI: 10.1111/j.1476-5381.1996.tb15517.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytochrome P450 inhibitors on EDHF‐mediated relaxation in the rat hepatic artery

Abstract: 1 The possibility that the endothelium-derived hyperpolarising factor (EDHF) in the rat hepatic artery is a cytochrome P450 mono-oxygenase metabolite of arachidonic acid was examined in the present study. In this preparation, acetylcholine elicits EDHF-mediated relaxations in the presence of the nitric oxide (NO) synthase and cyclo-oxygenase inhibitors No-nitro-L-arginine (L-NOARG) and indomethacin, respectively.2 17-Octadecynoic acid (17-ODYA, 50 gM), a suicide-substrate inhibitor of the cytochrome P450 mono-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
64
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 32 publications
12
64
1
Order By: Relevance
“…Moreover, EDHF-mediated responses in renal arteries from SHR were markedly less sensitive to the gap peptides than were vessels from WKY rats (Büssemaker, unpublished observations). Although cytochrome P450 epoxygenases play a crucial role in EDHFmediated responses in some species, several studies, 35,36 including one performed using rat renal arteries, 37 have reported that the EDHF-mediated relaxation of vessels from WKY and Sprague-Dawley rats does not require the activation of a cytochrome P450 enzyme. Cytochrome P450 epoxygenases can, however, be induced by several pathways associated with the induction of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EDHF-mediated responses in renal arteries from SHR were markedly less sensitive to the gap peptides than were vessels from WKY rats (Büssemaker, unpublished observations). Although cytochrome P450 epoxygenases play a crucial role in EDHFmediated responses in some species, several studies, 35,36 including one performed using rat renal arteries, 37 have reported that the EDHF-mediated relaxation of vessels from WKY and Sprague-Dawley rats does not require the activation of a cytochrome P450 enzyme. Cytochrome P450 epoxygenases can, however, be induced by several pathways associated with the induction of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat hepatic artery, the possibility that EDHF could be an EET was excluded by the failure of synthetic EETs to relax the tissue and by the inability of 17-ODYA (an inhibitor of the EET-generating pathway) to antagonize EDHF-induced relaxations (Zygmunt et al, 1996a). Furthermore, proadifen and clotrimazole antagonized levcromakalim-induced relaxations in the rat hepatic artery (Zygmunt et al, 1996a) and inhibited K-currents in rat portal vein (Zygmunt et al, 1996b), a tissue in which there are no reports of EDHF as an endogenous factor.…”
Section: Discussionmentioning
confidence: 99%
“…Narins et al also found that in patients with stable CAD, adverse outcomes were more prevalent in patients with painful vs silent ischemia. 99 In a separate low-risk group of 116 medically managed patients with CAD, 39% had ambulatory evidence of ischemic ST segment depression, with 82% being silent. However, the incidence of cardiac events was not increased in the group with silent ischemia.…”
Section: Prognostic Significance Of Silent Myocardial Ischemiamentioning
confidence: 99%